PENGARUH MODEL CYRCLE LEARNING 5E TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA PEMBELAJARAN IPA MATERI SIFAT - SIFAT CAHAYA - Mariya Ulfa; Ririn Andriyani Kumala Dewi; Asrizal Wahdan Wilsa (STKIP Subang, 2025)
The cycle learning 5E learning model is a constructivism-based learning cocsisting of five, namely engage (arousing intrest), explore (exploration), explain (explanation), elaborate (elaboration), and evaluate (evaluation). This model aims to facilitate active and collaborative learning where students build theirown knowledge through exploration and experimentation. This study aims to test the effect of thr Cycle Learning 5E model on students’ science process skills and improve science process skills through thr Cycle Learning 5E model. This research was conducted at SDN 1 Bungko in November 2024. The population in this study were all grade V of SDN 1 Bungko whilw the sample was class VA and class VB students. The method used in thid study was a quasi-experimental research essay pretest–posttest control group design. This desaign consis of two groups selected randomly then the experimental group was given science learing treatment with the 5E Learning Cycle model, whilw the control group was given a conventional model. The instrument used in the study was in the from of science process skill test questions. The results of the research obtained and the results of thr statistical tests carried out obtained an average posttest score of the experimental class of 44, 79 higher than the average posttest control scorenof 28,33. This is proven by the results of the statistical test using the t test, the sig value was obtained (2-tailed) 0,00 value α = 0,05. So it can be stated that there is an influence of the Cycle Learning 5E learning model based on the results of the study it can be concluded that there is an influence of the Cycle Learning 5E learning model on self-sensing pixess skils.